246 Clinicopathologic and genomic correlates of tumor mutational burden and its impact on PD-(L)1 inhibition efficacy in non-small cell lung cancer according to different PD-L1 expression subgroups. (9th November 2020) - Ricciuti, Biagio; Mahadevan, Navin; Umeton, Renato; Alessi, Joao; Polio, Andrew; Vokes, Natalie; Leonardi, Giulia; Aguilar, Elizabeth; Recondo, Gonzalo; Lamberti, Giuseppe; Lawrence, Marissa; Janne, Pasi; et al.
Abstract : Background: High tumor mutational burden (TMB) and PD-L1 expression are associated with improved clinical outcomes in patients (pts) with non-small cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs). However, how TMB performs as a predictive biomarker to ICIs in different PD-L1 expression subgroups is not well characterized. Methods: We collected clinicopathologic and genomic data from NSCLCs which underwent targeted NGS and TMB assessment at DFCI. An unbiased recursive partitioning (URP) algorithm was used to investigate an optimal TMB cut-off with respect to objective response rate (ORR) in the subset of pts treated with ICIs. This TMB cut-off was then validated in the prospective POPLAR/OAK cohort. Results: Among 3560 NSCLCs identified, median TMB was significantly higher among current smokers compared to former (P<0.0001) and never smokers (P<0.0001), and there was a significant correlation between TMB and pack-years (figure 1A-B). Pts with BRAF or KRAS mutations had the highest median TMB (10.9 and 9.8 mutations/Megabase [mut/Mb], respectively), while tumors with RET and ALK alterations had the lowest median TMB of 5.3 mut/Mb (figure 2A-B). Tumors with PD-L1 expression of ≥50% had significantly higher median TMB compared to those with a PD-L1 expression of 1–49% (P=0.002) and <1% (P<00001). Among pts treated with ICIs (N=690), URP identified an optimal grouping TMB cut-off for ORR of 19.0 mut/Mb, which corresponded to the 90th percentile. Pts with a TMB of ≥19.0 mut/Mb had a significantly higher ORR (45.2% vs 20.1%, P<0.0001) and longer median PFS (11.0 vs. 2.9 months, HR:0.49, P<0.0001) and OS (20.8 vs. 11.2 months, HR:0.59, P=0.001) compared to those with a TMB of <19.0 mut/Mb (figure 3A-C). A TMB of ≥19.0 mut/Mb was an independent predictor of improved PFS and OS at multivariable analysis (table 1). A TMB within the top 10th percentile was confirmed to correlate with improved ORR and PFS in atezolizumab arm but not in the docetaxel arm of the POPLAR/OAK trials (figure 4A-B). When TMB and PD-L1 where integrated in the URP, we identified an optimal cut-off of 19 mut/Mb among cases with a PD-L1 expression of ≤25%, and of 8.4 mut/Mb among those with a PD-L1 expression of >25%, suggesting that TMB differentially impacts response to immunotherapy among PD-L1 high versus low NSCLCs (figure 5). Conclusions: The impact of TMB may vary across PD-L1 expression subgroups. Rational integration of TMB and PD-L1 expression may identify NSCLCs with the greatest likelihood of response or resistance to ICIs. Ethics Approval: Clinicopathologic data were collected from patients with advanced NSCLC who had consented to a correlative research study (DF/HCC protocol #02-180).